Slope dependence of self-similar structure and entrainment in gravity currents - Salinas, Jorge S. (2022)
Results from seven direct and large-eddy simulations of gravity currents on slopes ranging from 0.14° to 2.86° that span from the subcritical to the supercritical regime are studied. By considering a long domain, attention is focused on the near-self-similar state approached by these currents far downstream. In the self-similar limit, the various shape factors, local Richardson number, entrainment coefficient, velocity scale and basal drag coefficient reach a constant value, while the current height, volume and momentum fluxes continue to increase linearly. Their dependence on slope is presented.